Prevalence of overweight and obesity in children and adolescents at large altitudes of the peruvian ande - Jo-Vargas, Nancy (2018)
Objetive: To determine the prevalence of overweight and obesity in children and adolescents of the Central Peruvian Sierra, in order to prevent the risk of cardiovascular diseases. Methods: 156 natives and residents between 06 and 16 years of age were studied from the rural population centers of La Victoria (4,097 masl) and Bellavista, (3,778 masl), from the province of Paurcartambo of the Department of Cerro de Pasco, of both sexes , coming from state schools. The nutritional status was evaluated using the Body Mass Index BMI or Quetelet index (Weight / height2). The obesity degrees of overweight, obese, severe obese and morbidly obese of the population in both genders were evaluated; Obesity was related to age, grouping children between 6 to 9 years of age, 10 to 12 and 13 to 16 years respectively. Similarly, sex was compared with the degree of obesity at different altitudes. Results: It was found that 81.4% (127/156) of the students presented a normal weight, 34.6% (54/156) in women and 46.8% (73/156) in men; 6.4% (10/156) of overweight, 3.8% in women and 2.6% in men, and 0.6% (1/156) obesity, corresponding to 0.0% in women and 0.6% in men. The age group 6 to 9 years old presented 32.1% (50/156) of normal weight, 1.9% (3/156) of overweight and 0.0% of obesity. Similarly, the age group of 10 to 12 years, presented 18.6% (29/156) 1.3% (2/156) and 0.6%, (1/166), respectively. The group of 13 to 16 years old, 30.8% (48/156) of normal weight, 3.2% (5/156) of overweight and 0.0% of obesity. The female gender that lives at 3778 and at 4.097 masl presented 12.2% (6/49) and 0.0% of overweight, respectively, with no cases of obesity. The male gender at 3778 and at 4.097 meters above sea level, presented 3.8% (2/52) and 6.1% (2/33) of overweight and 1.9% (1/52) and 0.0% of obesity, respectively. Conclusion: Overweight and obesity is not prevalent in children and adolescents of the Sierra Central Peruana, and research is still open to study the influence of factors typical of the region.   DOI 10.25176/RFMH.v18.n4.1735